Discourse analysis investigating processes of social construction - Phillips, Nelson; Hardy, Cynthia, 1956- (Thousand Oaks, [Calif.] ; London : SAGE, 2002)
'Discourse Analysis: Investigating Processes of Social Construction' reflects on the practice of analyzing discourse and the potential for revealing the processes of social construction that constitute social and organizational life.
Includes bibliographical references and index.
Specialized.
Description based on print version record.
Keywords: elektronické knihy; electronic books; Discourse analysis -- Social aspects